EFFECT OF AQUEOUS AND ALCOHOLIC EXTRACTS OF COTTONSEED ON SOME PARAMETERS OF SPERMS AND REPRODUCTIVE PERFORMANCE OF ALBINO MICE. - Ali, Inaam Noori; Fakhrildin, Mohammad Baqir M R; Al-Obaidi, Sabah A R (Al-Nahrain Journal of Science, 2010)
Two cottonseed extracts including alcoholic and aqueous at doses 20 and 40 mg/Kg/day wereorally administered to male mice for 6 weeks to study their effects on some of sperm parameters.Results showed that 20 and 40 mg/kg alcoholic and aqueous extract caused highly significant(P 0.01) decrease in the sperm concentration, motility (%) and progressive sperm motility (%).While, Results of the abnormal sperm morphology (%) for two treated groups 20 and 40 mg/kg/dayof alcoholic and aqueous extracts revealed a significant (P 0.05) increase after 6 weeks whencompared to the control group. Results revealed that the percentages of sperm agglutination werehighly significant (P 0.01) increased in mice treated with 20 and 40 mg/kg/day of alcoholic andaqueous when compared to the control. The fertility (%) and percentage of males of new bornbabies showed a significant (P 0.05) reduction in the treated mice as compared to female in thesame groups and to the control group. Meanwhile, a significant (P 0.05) increase in the recoverytime was showed with the increasing of doses of the two extracts when compared with the controlgroup.